Analisis Penerapan Kesehatan dan Keselamatan Kerja (K3) pada Karyawan Tim Masak Satuan Pelayanan Pemenuhan Gizi (SPPG) di Dapur X - Susan Almapirah; Safrizal Safrizal; Jun Musnadi Is; Perry Boy Chandra Siahaan; Ihsan Murdani (KOLONI, 2026)
The Nutrition Service Unit (SPPG) involves various potential occupational hazards, such as the use of sharp tools, exposure to heat, slippery floors, and the risk of gas leaks, making the implementation of Occupational Safety and Health (OSH) measures essential. Findings from research interviews with informants indicate that workers have experienced several occupational risks, including cuts from knives, exposure to hot oil splashes during frying, and skin conditions such as jock itch. This study aims to analyze the implementation of OSH among kitchen staff at the SPPG of Kitchen X. The study employed a descriptive qualitative method using the interactive analysis model. Informants consisted of the head chef, three kitchen team members, and the SPPG manager, selected through purposive sampling. Data were collected through interviews, observations, and documentation. The results indicate that OSH implementation has been fairly effective through the application of standard operating procedures (SOPs), the use of personal protective equipment (PPE), the provision of safety facilities, supervision, and periodic evaluations. Potential hazards identified included cuts, hot oil splashes, wet floors, and gas leaks. Compliance with PPE use was generally good, although there was still some inconsistency in the use of hairnets and aprons. It was concluded that OSH implementation at SPPG Kitchen X was already quite good; however, increased supervision and guidance are needed to strengthen the workplace safety culture.